2021
DOI: 10.1016/j.biomaterials.2020.120554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cellular and ECM aging on human iPSC-derived cardiomyocyte performance, maturity and senescence

Abstract: Cardiovascular diseases are the leading cause of death worldwide and their occurrence is highly associated with age. However, lack of knowledge in cardiac tissue aging is a major roadblock in devising novel therapies. Here, we studied the effects of cell and cardiac extracellular matrix (ECM) aging on the induced pluripotent stem cell (iPSC)-derived cardiomyocyte cell state, function, as well as response to myocardial infarction (MI)-mimicking stress conditions in vitro.Within 3-weeks, young ECM promoted proli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 89 publications
6
64
0
Order By: Relevance
“…This indicates that adult PV leaflets may be intended to undergo pathological changes. On the other hand, young PV leaflets and PVICs upregulated many physiological protective proteins/genes, like heat shock protein 90 alpha family class A member 1 (HSP90AA1, related to cellular response and recovery), SPP1 (related to bone resorption), and beclin 1 (BECN1, related to autophagy), which have been demonstrated to be beneficial for directly protecting valve cells or slowing down the pathological progression through a compensatory mechanism 36 39 . Balaoing et al evaluated hemostatic protein regulation in AV tissues and porcine valve endothelial cells (PVECs) with age and reported that old AV leaflets expressed more von Willebrand factor (vWF), while PVECs from the young age group had more gene expression of vWF 40 .…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that adult PV leaflets may be intended to undergo pathological changes. On the other hand, young PV leaflets and PVICs upregulated many physiological protective proteins/genes, like heat shock protein 90 alpha family class A member 1 (HSP90AA1, related to cellular response and recovery), SPP1 (related to bone resorption), and beclin 1 (BECN1, related to autophagy), which have been demonstrated to be beneficial for directly protecting valve cells or slowing down the pathological progression through a compensatory mechanism 36 39 . Balaoing et al evaluated hemostatic protein regulation in AV tissues and porcine valve endothelial cells (PVECs) with age and reported that old AV leaflets expressed more von Willebrand factor (vWF), while PVECs from the young age group had more gene expression of vWF 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Extended culture times of PSC-CMs can improve some aspects of maturation [227], but can also increase an aging phenotype, with increased SA-β-gal activity, increased lipofuscin accumulation, and reduced mitochondrial membrane potential, which can be reversed with treatment with the antioxidant, ascorbic acid [228]. When human PSC-CMs are cultured with young, adult, or aged extracellular matrix proteins from mice, young ECM increases PSC-CM proliferation, adult ECM enhances PSC-CM function, and aged ECM produces an aging phenotype with reduced PSC-CM function and lipofuscin accumulation, increased SA-β-gal activity, and increased ROS levels [229], suggesting that extracellular factors control transitions between proliferative, quiescent, and senescent phenotypes.…”
Section: Quiescence Versus Senescencementioning
confidence: 99%
“…Cell-free ECM is composed of the structural proteins as well as the secreted products of the resident cells [ 44 ]. Preservation of the ECM biochemical composition is crucial since ECM provides bioactive cues that affect cell response to its environment such as proliferation, migration, and differentiation [ 21 , 26 , 45 ]. Therefore, to ensure human cardiac tissue decellularization with the preservation of ECM bioactivity, we optimized previous decellularization methods [ 46 , 47 ] and used a combination of ionic and non-ionic detergent washes.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain naturally derived biomaterials recapitulating the biochemical cues in the native tissue environment, decellularization techniques have been developed and decellularized ECM (dECM) has become a preferred biomaterial for cardiac tissue engineering applications such as cardiac repair and regeneration [ 21 , 22 , 23 , 24 , 25 ]. In addition to being able to mimic the complexity of the native tissue and recreate a microenvironment with improved cell–cell connections and 3D cellular organization, the age of dECM was shown to affect cell response, thus by using dECM, the effect of age can also be introduced in the in vitro models [ 26 ]. Although dECM preserves the biochemical composition of the native tissue, it loses the mechanical and structural stability of tissue during the decellularization and digestion processes.…”
Section: Introductionmentioning
confidence: 99%